Pengaruh Kinerja Keuangan terhadap Sistem Informasi Akuntansi (SIA) pada Usaha Kecil Menengah (UKM) di Bandar Lampung - Meita Sekar Sari; Sugiyani Sugiyani (Mabsya: Jurnal Manajemen Bisnis Syariah, 2020)
"BPS-Statistics Indonesia, 2017: 23" State: economic development in Indonesia Small and Medium Enterprises (SMEs) are always described as a sector that has an important role. Described in Kompas.Com many Small and Medium Enterprises (SMEs) are developing at this time, that there are still a lot of Small and Medium Enterprises (SMEs) actors who do not realize the importance of neat financial records and bookkeeping, most of the Small and Medium Enterprises (SMEs) actors are still " blind "accounting. As a result, it is natural that many of them do not have a bookkeeping business that has the potential to grow. This type of research is quantitative with a collaborative research design. The population in this study are all small and medium businesses in Bandar Lampung, which have been recorded at the Central Statistics Agency (BPS) of Lampung province, amounting to 278 SMEs. Respondents obtained and used in this study were 55 SMEs. Analysis of the data used in this study is the classic assumption test and multiple regression analysis using the simultaneous test (Fcount test) and persial test (t test). The results showed that the output results can be seen that the calculated F value of 5020, when compared with the value of the table f of 2.40, then F count> F table then the Cash Ratio, Current Ratio, Return On Assets, Return On Equity, and Net Profit Margin together with the accounting information system is accepted, H0 is rejected. T Test results show that Cash Ratio, Current Ratio, Return On Equity (ROE), and Net Profit Margin significantly influence the Accounting Information System (AIS), while Return On Assets do not significantly influence the Accounting Information System (SIA). The results of multiple linear regression analysis showed the coefficient of determination (R Square) of 0.705 or 70.50% which means that changes that occur in the accounting information system (SIA) (Y) can be explained by the variable Cash Ratio, Current Ratio, ROA, ROE, and NPM (X1, X2, X3, X4, and X5) of 70.50%, and the remaining 29.50% is explained by other variables not proposed in this study.